MEASURING OF THE MODULE OF THE THREE-PHASE SYSTEM OF THE EDUCATIONAL SYSTEM μLAB - Ladislav, RUDOLF; TVARUZKA, Vaclav (Trends in education, 2008)
The story is about using the module of the three-phase system in education of the special subjects. The module makes a new part of the micro laboratory RC2000 system. The three-phase system presents a connection of three-phase electric power supply and load. Supply is the out of three-phase harmonic voltage generator controlled by a processor. Load or the appliance is possible to connect to a star or a triangle. Students can connect and measure this load also as a symmetrical or non-symmetrical one. It's possible to display measured values on the computer and then save them to the computer memory and at least evaluate. The three-phase module is small and it allows, in reduced scale, find values of currents and voltage in the three-phase system. The educational system μLAB is, in connection with the three-phase module, safe and visual, that's why it has big exercise in education of the special subjects.
Keywords: Module; three-phase system; computer; electric power supply; phase and line to-line voltage; symmetrical resistance load; non-symmetrical impedance load; phase and line to-line current.